Formation evaluation for Mishrif Formation in Selected Wells from Noor Oilfield - E. Nasser, Midhat; N. Ali, Sameer; Mohammed Saeed, Zainab M. (Iraqi Journal of Science, 2025)
This study aims at making formation evaluation for Mishrif Formation in three wells within Noor Oilfield which are: No-1, No-2 and No-5. The study includes calculations of shale volume and porosity, water saturation using Archie method, measuring the bulk volume of water (BVW) and using Buckle plot, as well as measuring the movable and residual hydrocarbons. These calculations were carried out using Interactive Petrophysics (IP) version 3.5 software as well as using Petrel 2009 software for structural map construction and correlation purposes. It was found that the Mishrif Formation in Noor Oilfield is not at irreducible water saturation, though it is of good reservoir characteristics and hydrocarbon production especially at the upper part of the formation.